Measurement of some characteristics of the BEGe detector - Loat, Bui Van; Anh, Le Tuan; Thanh, Dong Van; Nghia, Nguyen The; Khue, Pham Duc (VNU Journal of Science: Mathematics - Physics; Vol 28 No 1, 2012)
Abstract : Nowadays, semiconductor detectors, in general, and high purity gemanium detectors (HPGe) in particular are widely used in various fields of experimental nuclear physics. In gamma ray experiments, energy resolution and the efficiency are very important characteristics of detectors. In this paper, the gamma standard sources such as 137 Cs, 57 Co, 60 Co, 54 Mn, 133 Ba, and 109 Cd were used to study the characteristics of the BEGe 3050 detector. The methods of determining the absolute photo- peak efficiency and the dependence of the energy resolution on γ-ray energy are presented.